2013
DOI: 10.4103/0976-7800.119000
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of fixed dose combination of metoprolol and amlodipine in Indian patients with essential hypertension

Abstract: Background:This open-labeled, post-marketing study was conducted to assess the efficacy and tolerability of fixed dose combination of amlodipine and metoprolol extended release capsules in mild to moderate hypertension in adult Indian patients.Materials and Methods:Of 101 enrolled patients, 64 drug naïve patients were treated with regimen A (amlodipine 5 mg + metoprolol 25 mg) and those with prior history of hypertension (n = 37) were treated with regimen B (amlodipine 5 mg + metoprolol 50 mg) for 8 weeks. Tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…[ 285 ] Furthermore, some patients require a combination of two drugs in order to achieve a recommended BP target. Several Indian studies evaluated the efficacy of some FDCs: losartan 50 mg plus ramipril 2.5 mg vs each alone,[ 587 ] metoprolol extended release (XL) plus amlodipine vs losartan plus amlodipine,[ 588 ] metoprolol and amlodipine,[ 589 ] and reported that the FDCs were effective, safe and well-tolerated in patients with hypertension. …”
Section: Anagementmentioning
confidence: 99%
“…[ 285 ] Furthermore, some patients require a combination of two drugs in order to achieve a recommended BP target. Several Indian studies evaluated the efficacy of some FDCs: losartan 50 mg plus ramipril 2.5 mg vs each alone,[ 587 ] metoprolol extended release (XL) plus amlodipine vs losartan plus amlodipine,[ 588 ] metoprolol and amlodipine,[ 589 ] and reported that the FDCs were effective, safe and well-tolerated in patients with hypertension. …”
Section: Anagementmentioning
confidence: 99%